Advances in the Prevention of Low Birthweight. Proceedings from an International Symposium (Cape Cod, Massachusetts, May 8-11, 1988) - National Center for Education in Maternal and Child Health, Washington, DC.; Berendes, Heinz W.; National Center for Education in Maternal and Child Health, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This proceedings document contains papers addressing trends, determinants, and interventions in preventing low birthweight. Papers have the following titles and authors: "Trends in Rates of Low Birthweight in the United States" (Mary McCormick); "Evolution of the Preterm Birth Rate in France" (Gerard Breart); "The Etiology and Prevention of Low Birthweight: Current Knowledge and Priorities for Future Research" (Michael Kramer); "Support and Stress during Pregnancy: What Do They Tell Us about Low Birthweight?" (Jeanne Brooks-Gunn); "Results of a Three-Year Prospective Controlled Randomized Trial of Preterm Birth Prevention at the University of Pittsburgh" (Eberhard Mueller-Heubach); "Decrease and Rise in Rates of Preterm Deliveries: Haguenau Prenatal Study, 1971-1988" (Emile Papiernik et al.); "The West Los Angeles Prematurity Prevention Project: A Progress Report" (Calvin Hobel et al.); "The South Carolina Multicentered Randomized Controlled Trial To Reduce Low Birthweight" (Henry Heins et al.); "A Prematurity Prevention Project in Northwest North Carolina" (Paul Meis et al.); "The Family Workers Project: Evaluation of a Randomized Controlled Trial of a Pregnancy Social Support Service" (Brenda Spencer); "The Social Support and Pregnancy Outcome Study" (Ann Oakley and Lynda Rajan); "Prevention of Preterm Deliveries by Home Visiting System: Results of a French Randomized Controlled Trial" (Beatrice Blondel et al.); "Smoking Interventions during Pregnancy" (Mary Sexton); "Cervical Cerclage: New Evidence from the Medical Research Council/Royal College of Obstetricians and Gynecologists" (Adrian Grant); "Prevention of Intrauterine Growth Retardation with Antiplatelet Therapy" (Serge Uzan); "Does Calcium Supplementation Reduce Pregnancy-Induced Hypertension and Prematurity?" (Jose Villar); "Magnesium Supplementation in Pregnancy: A Double-Blind Study" (Ludwig Spatling); "An Overview of Trials of Social Support during Pregnancy" (Diana Elbourne and Ann Oakley); "Inhibition of Preterm Labor: Is It Worthwhile?" (Marc Keirse). Appendixes provide the symposium program and list of participants. (DB)
Availability: National Maternal and Child Health Clearinghouse (NMCHC), 38th and R Streets, N.W., Washington, DC 20057 (single copies free).
Sponsoring Agency: National Inst. of Child Health and Human Development (NIH), Bethesda, MD.
Sponsoring Agency: Health Resources and Services Administration (DHHS/PHS), Rockville, MD. Bureau of Maternal and Child Health and Resources Development.
Contract Number: MCU-117007.
Researchers.
Practitioners.
Keywords: Birth Weight; Congenital Impairments; Etiology; Infants; Medical Research; Neonates; Nutrition; Perinatal Influences; Pregnancy; Premature Infants; Prenatal Influences; Prevention; Preventive Medicine; Smoking; Social Support Groups; Stress Variables; Collected Works, Proceedings